Cyclosporine A and amlodipine induced gingival overgrowth in a kidney transplant recipient: case presentation with literature review. Issue 5 (28th May 2019) - Nanda, Tarun; Singh, Baljeet; Sharma, Parul; Arora, Karandeep Singh
Abstract : Drug-induced gingival overgrowth is a condition caused by side effects of treatment with one of three types of drugs: phenytoin (used in epilepsy treatment), cyclosporine A (used in transplantology after allogenic organ transplants) and calcium channel blockers (used in the treatment of hypertension). Gingival overgrowth leads to inflammation within the gums and periodontium and can amplify the existing periodontal disease leading to tooth loss. Patients who have undergone kidney transplant are given immunosuppressants to prevent transplant rejection and mostly it is accompanied with calcium channel blockers to treat hypertension associated with kidney transplant. This article reports a case of recent gingival enlargement associated with cyclosporine A and amlodipine given to a kidney transplant patient from the past 11 years.